KNOWLEDGE AND ATTITUDES RELATIONS WITH THE BEHAVIOR FAMILY ON THE SUPPRESSION OF MOSQUITO WITH THE GENESIS DENGUE FEVER IN GEDANGAN TAMBAK REJO: KNOWLEDGE AND ATTITUDES RELATIONS WITH THE BEHAVIOR FAMILY ON THE SUPPRESSION OF MOSQUITO WITH THE GENESIS DENGUE FEVER IN GEDANGAN TAMBAK REJO - Prianzah, Bayu Nova (Well Being, 2017)
Mosquito nest eradication dengue fever is the eradicate eggs , larva and pupæ mosquito with dengue fever (aedes aegypti) in places.The purpose of psn outbreak is to control population aedes aegypti mosquito , so that transmission of dengue fever preventable or reduced .Dengue fever prevention is highly dependent on vektornya control , namely aedes aegypti mosquito .The purpose of this research is to know what is the relationship knowledge and attitude with the behavior family on the suppression of mosquito nests (psn) with the genesis dengue fever in the work area of puskesmas farms rejo .Design research used is correlation with the approach cross sectional while technique the sample collection of sampling quota . The number of respondents you got 30 of 59 residents in hamlet gedangan .The results show that respondents penelitia of knowledge less 16 respondents (53.3 %) , some of the attitude of respondents were positive about 18 respondents (60.0 %) and head of family behave well as many as 15 respondents (50.0 %) .The correlation knowledge by behavior ( 0.000 & lt; 0.05 and correlation attitude with behavior ( 0.001 & lt; 0.05 and the results of logistic regression is closely to do knowledge and attitude with the behavior family in mosquito nest eradication so h1 accepted.